International mutual relations with the USA - Chupekov, A. A.; Taubaldy, Z. S. (Journal of Oriental Studies, 2016)
In this article open up international mutual relations with the USA. As a result of the second world war financially economic state and military force of the USA became considerably stronger. Realizing war facilities the American monopolists began to acquire an enormous benefit. The production capacity of industry very grew.